Interview with Nooni Reatig, Washington, D.C. architect - Summer, Rebecca (My University, 2018)
This interview was conducted as part of Rebecca Summer's research for the dissertation "The Urban Alley: A Hidden Landscape of Social Change in Washington, D.C." Reatig is an architect and developer at Suzane Reatig Architecture, a firm in the Shaw neighborhood of Washington, D.C. Shaw is home to two popular alleys: Blagden Alley and Naylor Court. The interview covers the history of the Reatig firm and its activity in Shaw. The firm is know for its very colorful/color block modern designs. There is also discussion of broader changes over time to development in Shaw, alley-facing design, new developments in Blagden Alley.
This interview was conducted as part of Rebecca Summer's research for the dissertation "The Urban Alley: A Hidden Landscape of Social Change in Washington, D.C." Reatig is an architect and developer at Suzane Reatig Architecture, a firm in the Shaw neighborhood of Washington, D.C. Shaw is home to two popular alleys: Blagden Alley and Naylor Court. The interview covers the history of the Reatig firm and its activity in Shaw. The firm is know for its very colorful/color block modern designs. There is also discussion of broader changes over time to development in Shaw, alley-facing design, new developments in Blagden Alley.
Keywords: Research Subject Categories::SOCIAL SCIENCES; architecture; urban design; alleys; Washington, D.C.